Erosion of repaired exstrophy bladder by a large vesical calculus - Abdul Hai; Arvind Sinha; Mayank Bisht; Neelkamal Gola (Wolters Kluwer Medknow Publications, 2011)
Formation of stones in repaired exstrophy bladder is common; however, erosion of stone through the repaired bladder and anterior abdominal wall has never been reported. We report one such case of erosion after three years of repair.